THE INFLUENCE OF HYDRODYNAMIC FACTORS ON CHARACTERISTICS OF SUSPENDED SEDIMENT DISTRIBUTION IN THE MEKONG RIVER MOUTH AREA - Tien, Nguyen Ngoc (Vietnam Journal of Marine Science and Technology, 2015)
This paper presents some research results on the distribution characteristics of suspended sediment in coastal waters of Mekong river under the influence of hydrodynamic factors by using numerical model. The model was built on unstructured grid and calibrated with observed data to verify water levels at My Thanh, Thuan An stations. The calculated results showed the role of wind, wave, river discharges during both the rainy and dry seasons, and water level fluctuation to the distribution characteristics of suspended sediment in coastal waters of Mekong river mouth area. Accordingly, under the influence of waves, wind, the concentration of suspended sediment in the flood tidal phase was enhanced from the bottom floor to the surface, and a significant increase in turbidity occurred off Mekong River mouth. On the other hand, the distributions of suspended sediment concentration in tributaries were different, and depended on the tidal fluctuations.